The Immunological Role of Interleukin-10 in Chronic Renal Disease Patients of Thi-Qar Province - Mousa, Hind; Dhuha A. Al-Sattar Jabar, (University of Thi-Qar Journal of Science, 2024)
Chronic renal disease (CRD) is a basic worldwide health issue; the interleukin-10 is an anti-inflammatory mediator that has a role in normal kidney function and in the progression of chronic renal failure. This study aims to measure the serum level of anti-inflammatory cytokines (IL-10), and evaluate its role in the progression of chronic kidney disease (CRD). The study comprised 66 patients divided into group 1 (22 subjects with CKD) and 2 (22 CRD patients with Diabetic mellitus name as DM-CRD), and group 3 (22 patients with Diabetic mellitus DM only without CRD). In addition to 22 consider as healthy people as control. The serum levels of IL-10 were determined by using ELISA assay. The results demonstrated a significant increase in the serum means levels of IL-10 in all patient groups (CKD, DM-CKD, DM) in comparison with healthy control, while there was   nonsignificant difference in its mean serum levels among all patient groups. It was concluded that male and aging are predisposing factors to chronic renal disease, and elevated levels of IL-10 in patients with CKD and diabetes  reflect the potential role of IL-10 in the progression of diabetic nephropathy patients to chronic renal disease